Badan Permusyawaratan Desa Dalam Tiga Periode Pemerintahan Di Indonesia - Emilda Firdaus (Fakultas Hukum Universitas Riau, 2010)
Historically village represent will form of politicalsociety and the governance in Indonesia far beforethis nation and state is formed. Social structure of akind the village, socialize custom and others have cometo social institution having very important position.In order to to realize autonomy and democratize atthe village governance, hence need there is cleararrangement and this specially to existence BPD ineach regency in Indonesia. In three governance periodin Indonesia that is from Orde Lama period, period ofOrde Baru and Reform Order have acknowledgedlegislative body and village governance system ofvillage although own difference in the form of itimplemented.